(untitled) (Journal of Engineering, 2024)
In this work a high-speed turbopumps of (22000 rpm) rotational speed, which are oxidizer and fuel turbopumps, are designed. The design requirement for mass flow rate and outlet pressure are (12.5 kg/s) and (113×10 Pa) respectively for the oxidizer turbopump, and (3.5 kg/s) and (95x10 Pa) respectively for the fuel turbopump. The design work of centrifugal pump is divided into impeller and volute design works. The impeller design work is performed by the streamline curvature and quasi-orthogonal technique based on hub-to-shroud mean stream surface between two blades with assistance of experimental design coefficients and relations for first prediction. The volute is designed by using the method of constant angular momentum, where in this method the tangential and radial velocities are considered uniform around the impeller. The numerical results are compared with experimental data of the actual pumps, and it is found that these results agree well with the real designs. The output of the design program is used as an input to the performance program. The performance prediction is achieved by three dimensional, steady, incompressible and viscous flow analyses through the blade passage. The ANSYS program has been employed to solve these equation in order to predict the flow characteristics at design and off-design conditions. The analysis is done at many operation conditions, which have the range of flow coefficient ratio (ФФ) from (0.4) to (1.8), and the results are compared with experimental results for previous work to make sure the validity of the analysis program at design and off-design conditions.